2011
DOI: 10.1016/j.anai.2010.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of asthma management, socioeconomic status, and medication insurance characteristics to exacerbation frequency in children with asthma

Abstract: Background-Less than 25% of asthmatic children are well controlled.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
59
1
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(65 citation statements)
references
References 33 publications
3
59
1
2
Order By: Relevance
“…This result is in accordance with that of Zedan et al (2013) who found that asthma symptom was insignificantly related to the age and gender of asthmatic children, with that of Ungar et al (2011) who found that asthma were more predominant in boys especially those younger than 10 years old, and with that of Pradel et al ( 2001) who found that older children have less severe asthma symptom and better control than younger children, and Petsios et al (2013) who also found that asthma was more severe in boys than girls. In contrast to two other in which they found that girls have more severe asthma symptom then the boys (Van De Ven, Engels, Sawyer, Otten, & Van Den Eijnden, 2007;Nordlund, Konradsen, Pedroletti, Kull, & Hedlin, 2011) ).…”
Section: Resultssupporting
confidence: 81%
“…This result is in accordance with that of Zedan et al (2013) who found that asthma symptom was insignificantly related to the age and gender of asthmatic children, with that of Ungar et al (2011) who found that asthma were more predominant in boys especially those younger than 10 years old, and with that of Pradel et al ( 2001) who found that older children have less severe asthma symptom and better control than younger children, and Petsios et al (2013) who also found that asthma was more severe in boys than girls. In contrast to two other in which they found that girls have more severe asthma symptom then the boys (Van De Ven, Engels, Sawyer, Otten, & Van Den Eijnden, 2007;Nordlund, Konradsen, Pedroletti, Kull, & Hedlin, 2011) ).…”
Section: Resultssupporting
confidence: 81%
“…However in a study by Ungar et al [43] in the Canadian universal healthcare system found that families with a medium or high income adequacy had 28% fewer exacerbations as compare to those with a low income adequacy. The study from Ungar et al [43], in a single payer system, depicted that despite universal healthcare coverage, asthma may not be adequately managed in the socially disadvantaged.…”
Section: Asthmamentioning
confidence: 99%
“…The risk of exacerbations is increased in children with inadequate adherence to controller therapy, poor asthma control, frequent prior exacerbations and elevated FeNO levels, but none of these factors reliably predict exacerbations [82][83][84][85]. Obviously, severity, frequency and management of exacerbations outlined in an asthma action plan should be reviewed at each consultation.…”
Section: Exacerbationsmentioning
confidence: 99%